Direct Observation of Conductive Polymer Induced Inversion Layer in n‐Si and Correlation to Solar Cell Performance. (30th October 2019) - Wang, Rongbin; Wang, Yusheng; Wu, Chen; Zhai, Tianshu; Yang, Jiacheng; Sun, Baoquan; Duhm, Steffen; Koch, Norbert
Abstract: Heterojunctions formed by ultrathin conductive polymer [poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate)—PEDOT:PSS] films and n‐type crystalline silicon are investigated by photoelectron spectroscopy. Large shifts of Si 2p core levels upon PEDOT:PSS deposition provide evidence that a dopant‐free p–n junction, i.e., an inversion layer, is formed within Si. Among the investigated PEDOT:PSS formulations, the largest induced band bending within Si (0.71 eV) is found for PH1000 (high PEDOT content) combined with a wetting agent and the solvent additive dimethyl sulfoxide (DMSO). Without DMSO, the induced band bending is reduced, as is also the case with a PEDOT:PSS formulation with higher PSS content. The interfacial energy level alignment correlates well with the characteristics of PEDOT:PSS/n‐Si solar cells, where high polymer conductivity and sufficient Si‐passivation are also required to achieve high power conversion efficiency. Abstract : The formation of an inversion layer within n‐Si near the interface with poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) based conductive thin films is evidenced. High power conversion efficiency in solar cells is correlated with a large contact‐induced band bending in Si, high polymer conductivity, and proper Si interfacial passivation.